Yeasts and others parameters of pollution of the Ribeirão Claro stream in Rio Claro, São Paulo - Peçanha, Marcela Pellegrini [UNESP]; Pagnocca, Fernando Carlos [UNESP]; Rugani, Célio Augusto [UNESP]; Neves, Fátima Aparecida [UNESP] (My University, 1996)
The main water source of the Rio Claro municipal district (DAAE) was analysed for determining the level of organic contamination. Temperature, pH, light penetration, conductivity, dissolved oxygen, total dissolved phosphate, ortophosphate, ammonia, heterotrofic bacteria, total coliforms, fecal coliforms, total yeasts and fermentative yeasts were analysed during one year with samples being collected on a monthly basis. Bathing quality of the water from sites 1, 2 and 3 were classified, respectively, as Satisfactory, Very Good and Improper based on fecal coliform counts. Total yeast counts were appropriate as a complement for the appraisal of fresh water contamination by coliform counts. Seventeen yeast species belonging to genera Candida, Cryptococcus, Kloeckera, Pichia and Rhodotorula were found but none of them could be correlated with a level of contamination. Candida famata, C. robusta - like and C. colliculosa were isolated at all of the sites and between the five species found only at the more polluted site, Rhodotorula mucilaginosa was prevalent.
Keywords: Coliforms; Water contamination; Yeasts